Regards idéographiques sur la France et la langue française dans l’écriture transculturelle de Shan Sa - Fiorella Di Stefano (Carnets)
At beginning of XX century the passion for « chinoiserie » throughout French poets has undoubtedly furnish a fake image about Easter lands behind the notion of « Orientalism » forged by Said. Actually, France and French language as country and language of adoption seem to rise up a new idea of Europe in francophone writers and artists. We can mention for example the new literary perspectives including in Chinese-francophone writers such as François Cheng, Dai Sijie, Shan Sa who are very much involved in offering to European readers a new idea of China. However theirs works contributes to develop a new idea of Europe in the world. In this paper we focuses about Chinese- francophone writing as way to light on an “exotic” image of Europe.